MENEBAR UPAYA, MENGAKHIRI KELANGGENGAN: PROBLEMATIKA PERKAWINAN ANAK DI NUSA TENGGARA BARAT - Ida Rosyidah; Iklilah Muzayyanah Dini Fajriyah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
This paper elaborates on the problematic practices of under-aged marriage, or also known as child marriage, rifing in West Nusa Tenggara, as well as the state and society’s efforts to eliminate the phenomenon. Child marriages are assumed to be problematic because it relates to unfinished school years, marginalizing women from the economic activities, domestic violence on women, and sexual reproduction matters. Women become the main vulnerable victims in this concern, since their social position is less than their counterparts especially in the cultural aspect of domestic area. This paper is part of research on the implementation of article 2 (2) and Article 7 (1) of Law No. 1 of 1974 on Marriage in KUA NTB. Using qualitative perspectives, this research was conducted in 2012 using data collection methods of in-depth interviews, focus group discussion, observations, and literature studies to gain women’s perspectives concerning the issue. The result showed factors causing child marriages are economy, morality, technology, social and cultural pressures, and lack of legal awareness. In the cultural context, merarik had been misinterpreted and instead, it contributed to the high amoung of child marriages. Child marriage is understood in many different ways. From government’s perspective, child marriage is a violation against law. On the other hand, the society doesn’t see the essential problem to child marriage. Marriages are fate and a part of the human life cycle that cannot be avoid, regardless of age. However, some other people realize that child marriage could potentially hurt the future of the children involved in the marriage, especially the girls and it is considered to be the reason to high numbers of divorces and remarriages in West Nusa Tenggara. To minimize the practice of child marriages, various efforts have been made by the government and society. Among those, the government holds a free istbah marriage and offers counseling of the impact of early marriage for society. Besides the government, traditional leaders, religious leaders, and NGOs are increasingly trying to do dissimenation, awareness, and advocacy programs to promote the risks of child marriage, some of which includes interactive discussions, seminars, talk shows, music festivals, and researches on child marriage with or without cooperation other institutions.